2022
DOI: 10.1186/s10194-022-01416-w
|View full text |Cite
|
Sign up to set email alerts
|

FKN/CX3CR1 axis facilitates migraine-Like behaviour by activating thalamic-cortical network microglia in status epilepticus model rats

Abstract: Background The incidence of migraines is higher among individuals with epilepsy than in healthy individuals, and these two diseases are thought to shared pathophysiological mechanisms. Excitation/inhibition imbalance plays an essential role in the comorbidity of epilepsy and migraine. Microglial activation is crucial for abnormal neuronal signal transmission. However, it remains unclear whether and how microglia are activated and their role in comorbidities after being activated. This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Most murine studies investigated purinergic receptors (e.g., P2X/P2Y), which is plausible given the metabolic aspects of migraine pathophysiology, including neuronal energy de ciency (20). The involvement of the fraktalkine pathway was only recently suggested in another mouse model of migraine and was also associated with impaired neuronal signalling in thalamo-cortical networks (21). We found that CX3CL1, the ligand to the fractalkine receptor, is increased in humans irrespective of the headache status.…”
Section: Serum T-tau As a Potential Biomarker For Disease Activity In...mentioning
confidence: 62%
“…Most murine studies investigated purinergic receptors (e.g., P2X/P2Y), which is plausible given the metabolic aspects of migraine pathophysiology, including neuronal energy de ciency (20). The involvement of the fraktalkine pathway was only recently suggested in another mouse model of migraine and was also associated with impaired neuronal signalling in thalamo-cortical networks (21). We found that CX3CL1, the ligand to the fractalkine receptor, is increased in humans irrespective of the headache status.…”
Section: Serum T-tau As a Potential Biomarker For Disease Activity In...mentioning
confidence: 62%
“…The surgical procedure was conducted as described previously [ 34 , 35 ]. Rats were anesthetized with a ketamine-xylazine mixture (100 mg/kg ketamine, 10 mg/kg xylazine) and fixed on a stereotaxic apparatus (68,002, RWD Life Science).…”
Section: Methodsmentioning
confidence: 99%
“…After the IS (or saline) injection, we immediately recorded the number of head scratching for 1 h, which represented a nociceptive behavior resulting by IS. The periorbital mechanical threshold was evaluated by a von Frey test, using an up-and-down approach according to previous report [ 33 , 34 ]. A positive reaction was defined as rapid withdrawal of the head.…”
Section: Materials and Methodsmentioning
confidence: 99%